Public health emergency preparedness a practical approach for the real world - McKinney, Suzet; Papke, Mary Elise (Jones & Bartlett Learning, 2019)
"This is a widely offered upper level undergrad and grad level course. Will bundle perfectly with our PH Disaster Casebook by Linda Landesman. Will be a gritty practical text"--Provided by publisher